Robustness of the exponential dichotomies of boundary-value problems for the general first-order hyperbolic systems - Kmit, I.Ya.; Recke, L.; Tkachenko, V.I. (Український математичний журнал, 2013)
We examine the robustness of exponential dichotomies of boundary-value problems for general linear first-order one-dimensional hyperbolic systems. It is assumed that the boundary conditions guarantee an increase in the smoothness of solutions in a finite time interval, including the reflection boundary conditions. We show that the dichotomy survives in the space of continuous functions under small perturbations of all coefficients in the differential equations. Вивчається грубiсть експоненцiальної дихотомiї для крайових задач для загальних лiнiйних гiперболiчних систем першого порядку. Припускається, що крайовi умови забезпечують пiдвищення гладкостi розв’язкiв за скiнченний промiжок часу, що дозволяє також розглядати умови вiдбиття вiд межi областi. Показано, що дихотомiя зберiгається у просторi неперервних функцiй при малих збуреннях всiх коефiцiєнтiв диференцiальних рiвнянь.